2021
DOI: 10.1111/irv.12855
|View full text |Cite
|
Sign up to set email alerts
|

Underlying cardiopulmonary conditions as a risk factor for influenza and respiratory syncytial virus infection among community‐dwelling adults aged ≥ 65 years in Thailand: Findings from a two‐year prospective cohort study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…With RSV vaccines now available for older adults, data on RSV incidence in community- dwelling older adults can inform population impact and models evaluating the potential benefits of RSV vaccination programs in older adults, although few of these studies exist, particularly before the COVID-19 pandemic. 6,8,16,28,29 Prior studies identified RSV illness by passive surveillance only 29 or evaluated incidence based on both virologic and serologic confirmed infection. 8 Korsten et al (RESCEU study) assessed annual RSV community burden in about 500 older adults :260 years old from three cities in Europe between 2017–19 by weekly emails or calls to identify ARI, which was defined as having at least one of the following symptoms: cough, nasal congestion or discharge, wheezing or shortness of breath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With RSV vaccines now available for older adults, data on RSV incidence in community- dwelling older adults can inform population impact and models evaluating the potential benefits of RSV vaccination programs in older adults, although few of these studies exist, particularly before the COVID-19 pandemic. 6,8,16,28,29 Prior studies identified RSV illness by passive surveillance only 29 or evaluated incidence based on both virologic and serologic confirmed infection. 8 Korsten et al (RESCEU study) assessed annual RSV community burden in about 500 older adults :260 years old from three cities in Europe between 2017–19 by weekly emails or calls to identify ARI, which was defined as having at least one of the following symptoms: cough, nasal congestion or discharge, wheezing or shortness of breath.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies have been conducted in households with children 6,[11][12][13] and in high-income countries. 14 Fewer were among older adults 15,16 including those aged ≥80 years, a group vulnerable to severe complications from these infections, 14 and in low-and-middle income countries. 12,[16][17][18] To address this gap, we established a community cohort of older adults in Jiangsu Province, China to characterize the incidence, symptom profiles, and medical care of PCR-confirmed influenza virus and RSV illnesses from December 2015-September 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of RSV in Thailand follow distinct spatiotemporal patterns with predictable seasonal timing and length [ 3 , 4 ]. During an RSV season, 60-70% of all children admitted with RSV infection are under the age of 12 months, while 80% are under the age of 2 years [ 5 - 7 ]. The clinical presentation of RSV infection usually begins with a runny nose, nasal congestion, and cough.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults with underlying cardiorespiratory and endocrine or metabolic conditions (such as chronic obstructive pulmonary disease [COPD], congestive heart failure, and diabetes) are at increased risk of RSV-ARI [ 7 , 8 ]. This population often has more severe clinical presentations that may require medical care and may lead to hospitalization, exacerbation of underlying conditions, or death [ 5 , 7–19 ].…”
mentioning
confidence: 99%